2014
DOI: 10.1016/j.cell.2014.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning Circadian Transcription by SIRT6 Leads to Segregated Control of Cellular Metabolism

Abstract: SUMMARY Circadian rhythms are intimately linked to cellular metabolism. Specifically, the NAD+-dependent deacetylase SIRT1, the founding member of the sirtuin family, contributes to clock function. Whereas SIRT1 exhibits diversity in deacetylation targets and subcellular localization, SIRT6 is the only constitutively chromatin-associated sirtuin and is prominently present at transcriptionally active genomic loci. Comparison of the hepatic circadian transcriptomes reveals that SIRT6 and SIRT1 separately control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
234
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(241 citation statements)
references
References 61 publications
2
234
0
Order By: Relevance
“…16,17 Moreover, multiple investigations have revealed that SIRT6 regulates the pathogenesis of various types of cancers, such as including hepatocellular carcinoma, breast cancer, and pancreatic cancer. [18][19][20] Molecular mechanism exploration further indicates that the diverse roles of SIRT6 in carcinogenesis are implemented through the regulation of cellular signals including ERK, Smad, and Raf/mitogen-activated extracellular signal-regulated kinase/extracellular signal-regulated kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Moreover, multiple investigations have revealed that SIRT6 regulates the pathogenesis of various types of cancers, such as including hepatocellular carcinoma, breast cancer, and pancreatic cancer. [18][19][20] Molecular mechanism exploration further indicates that the diverse roles of SIRT6 in carcinogenesis are implemented through the regulation of cellular signals including ERK, Smad, and Raf/mitogen-activated extracellular signal-regulated kinase/extracellular signal-regulated kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes, collectively referred to as sirtuins, have varied intracellular localization, being nuclear, cytoplasmic, or mitochondrial. Because they represent a direct molecular link between NAD + -dependent metabolism and deacetylase activity, the finding that both SIRT1 and SIRT6 contribute to circadian control has provided the first molecular link between metabolism, aging, and the circadian clock (31,32).…”
Section: Circadian Rhythms In the Chromatin Fibermentioning
confidence: 99%
“…20,21 In contrast, SIRT6 appears to be downregulated in other types of solid tumors (ie, gastrointestinal cancers, including colorectal and pancreatic cancer), which results in increased glycolysis, glucose uptake, and MYC activity. 18,22 To date, the role of SIRT6 in hematologic malignancies, including MM, is unknown. In this study, we have characterized the biological role, prognostic significance, and potential clinical relevance of SIRT6 expression in MM.…”
Section: Sirtuins (Sirts) Are Nadmentioning
confidence: 99%